The correlation between high sensitivity C-Reactive Protein level and the Extent of Coronary Lesion and Cardiac Systolic Function in Coronary Heart Disease (Faculty of Medicine Universitas Indonesia, 2003)
To determine the mean value of high sensitivity C-Reactive Protein (hs-CRP), association between plasma level of hs-CRP with extent of disease and systolic function. A cross sectional study had been conducted to 106 coronary artery disease patients (90 stable angina pectoris, 11 unstable angina pectoris and 5 acute myocardial infarction). Plasma quantitative level of hs-CRP with cor angiography to determine extent of disease and ejection fraction were measured. The mean of hs-CRP levels in patients with SVD were 5,5 ± 7,6 mg/L, DVD were 6,6 ± 21,7 mg/L and TVD were 5,5 ± 8,0 mg/L and p=0,056, respectively. There were no significant association between hs- CRP levels with extent of disease. Systolic function had negative correlation with levels of hs-CRP (p=0,015, r=-0,235). This study showed that plasma level of hs-CRP cannot reflect the extent of disease, and it had negative correlation with systolic function. (Med J Indones 2003; 12: 201-6)